2020
DOI: 10.3390/ma13153436
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the Residual Stresses and Fatigue Performance of Riveted Single Strap Butt Joints

Abstract: In aircraft manufacturing, riveting is one of the most important connection ways to fasten the sheet metal parts. The riveted single strap butt joints are mainly used in the load-bearing components of the aircraft such as the fuselage and wing panels. The connection quality and fatigue performance of the riveted joints directly affect the reliability and safety of the aircraft. In this paper, under the assumption of constant temperature, the fatigue strengthening mechanism of interference-fit riveting is intro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…The traditional types of mechanical joints mainly include a single-lap joint, a double-lap joint, a single-strap butt joint and a double-strap butt joint. The single-strap butt joint is the main structure of wing panels, which are used as load-bearing components [9].…”
Section: Introductionmentioning
confidence: 99%
“…The traditional types of mechanical joints mainly include a single-lap joint, a double-lap joint, a single-strap butt joint and a double-strap butt joint. The single-strap butt joint is the main structure of wing panels, which are used as load-bearing components [9].…”
Section: Introductionmentioning
confidence: 99%
“…Kumar et al [13] conducted nonlinear finite element analysis on riveted lap joints and found that as long as the rivet did not yield, the load distribution between rivets was not uniform, which may lead to local high stress and cracking. Liu et al [14] numerically studied the residual stresses distribution of single-band butt joints with different rivet sizes and thicknesses. There is little research on the influence of gap between sheets on riveting quality.…”
Section: Introductionmentioning
confidence: 99%